Fabricating an oxygen-vacancy-rich urchin-like Co3O4 nanocatalyst to boost peroxymonosulfate activation to degrade high-concentration crystal violet. Issue 18 (15th September 2022) - Li, Bo; Xu, Huan-Yan; Liu, Yu-Long; Dong, Li-Min; Komarneni, Sridhar
Abstract: Due to the in-situ generation of reactive oxygen species (ROS), sulfate radical-based advanced oxidation processes (SR-AOPs) have emerged for the oxidative degradation of organic contaminants. Developing highly efficient heterogeneous catalysts is of great importance for SR-AOPs. In this work, an urchin-like Co3 O4 nanocatalyst with oxygen vacancies (VO ) was elaborately fabricated and employed for enhanced peroxymonosulfate (PMS) activation to degrade the high-concentration active dye crystal violet (CV). The obtained sample was characterized by field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and N2 adsorption/desorption isotherms. Characterization results indicated that this unique VO -rich urchin-like Co3 O4 nanocatalyst was endowed with a larger surface area and abundant reactive sites for PMS adsorption and activation. The experimental results of CV degradation showed that nearly complete removal of 100 mg L −1  CV could be realized within 30 min of reaction time under neutral conditions at room temperature, and the degradation process followed retarded-first-order kinetics. Electron paramagnetic resonance (EPR) spectra accompanied by quenching experiments of radicals demonstrated that the contribution of ROS to CV degradation followed this sequence: 1 O2  > ▪OH > SO4 ▪-  > O2 ▪- . The degradation pathways of CV were proposed by a combination of density functional theory (DFT) calculations along with frontier orbit theory while the toxicity of intermediate products was evaluated by quantitative structure-activity relationship (QSAR) prediction. Graphical abstract: Image 1 Highlights: Oxygen-vacancy-rich urchin-like Co3 O4 was fabricated for PMS activation. Active radicals were confirmed by radical quenching tests and EPR technology. Radical 1 O2 dominated crystal violet degradation by a nonfree radical pathway. The degradation pathways of CV were simulated by DFT calculations. The toxicity of intermediate products was evaluated by QSAR prediction.